PERANAN SEKRETARIS DALAM MELANCARKAN TUGAS PERKANTORAN DI HOTEL MELIA BALI, NUSA DUA - Sagung Mas Suryaniadi (Forum Manajemen, 2013)
The main role of a secretary is to assist the manager or the leader ofthe company to do his job. Bisides a secretary is mean something to the otheremployee.There are many things a secretary should do in her job. For some reason a secretarycouldnâ€™t do their jobs and duties optimally even sometimes couldnâ€™t ï¬ nish some ofthem at all. Their reaserch is aim to the role of a secretary to do ofï¬ ce explorepractice at Melia Bali Nusa Dua.The problem for this reaserch is how much the role of a secretary could contribute to the job of ofï¬ ce practice at Melia Bali Nusa Dua. And the aim of this reaserch isto know more about secretaryâ€™s duties and how much she could complete them well.The result of this reaserch is to do some contribution to the process of curriculumdevelopment at Bussiness Administration Politeknik Negeri Bali.Data collection is done by interview, observation and questionnaire. The result isdescribed descriptionly. The result of the reaserch is 72,13% of secretaryâ€™s dutiesshown has important contribution to ofï¬ ce practice. It is said to be in good level ofstandard.